Implementation Curriculum Merdeka Belajar Learn Science And Social (Ipas) Learning In Elementary School: Perpective Teacher - Sulistyani Ramadhani (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Effective and relevant learning plays a key role in improving the quality of education in this modern era. One concept that is currently developing is "Freedom to Learn", which emphasizes individual empowerment in the learning process. The science and technology learning approach (Individual, Choice, Active and Systematic) is one of the strategies used in implementing the Independent Learning concept. The purpose of this article is to present regarding the implementation of science and social learning in the Merdeka Belajar context. This descriptive involves searching and analyzing related articles, journals and publications that discuss the concept of Merdeka Belajar and the science and science learning approach. The results of the literature review show that science learning applied in the Merdeka Belajar context provides a number of benefits for students. This approach gives individuals the freedom to choose materials, methods and learning tempo that suit their needs and interests. In this context, students become the main agents in their own learning process, which encourages intrinsic motivation and personal responsibility. Apart from that, science learning also encourages active involvement of students in the learning process. They are encouraged to be active participants in discussion, collaboration, and problem solving, which helps develop social skills, creativity, and critical thinking. This approach also involves self-evaluation, in which learners independently reflect on their progress and achievements, and make decisions that can improve their learning outcomes. However, the implementation of science and science learning in the Merdeka Belajar context also faces a number of challenges. Some of these challenges include the need to provide adequate support and training to educators to implement this approach effectively, the development of flexible curricula, and the development of infrastructure that supports learner-centered learning.